On Photography. The Medium, The Scandal and The Silence - Fiorentino, Giovanni (Recherches sémiotiques / Semiotic Inquiry)

(untitled) (Association canadienne de sémiotique / Canadian Semiotic Association, 2008)
Italo Calvino once referred to photography as an “anthropologically new object”, while Roland Barthes described it as a “bizarre medium”. In all accounts photography can be seen to resist our attempts to theorize it. Accepting this challenge, the present essay seeks to investigate the specificity of photography with reference to three concepts and pairs of authors: Ia.The concept of limit and the way it relates to photography and to short story writing as the latter is discussed by Julio Cortàzar and Italo Calvino.Ib.The concept of dematerialization, which surfaces as early as the nineteenth-century in separate essays on photography by Charles Baudelaire and Oliver Wendell Holmes.Ic.The concept of displacement, which emerges in the complementary thought and works of Marcel Duchamp and Man Ray.These concepts are then used to consider three photographs: a snapshot taken by an American soldier deployed in Iraq between 2003 and 2004; Le croci di Guerra (1991) by Oliviero Toscani for Benetton; and Dead Troops Talk (1992) by Jeff Wall.